Concurrency : state models and Java programs. - Magee, Jeff, ....-; Kramer, Jeff, ....- (Chichester : Wiley, 2006)
Concurrency provides a thoroughly updated approach to the basic concepts and techniques behind concurrent programming. Concurrent programming is complex and demands a much more formal approach than sequential programming. In order to develop a thorough understanding of the topic Magee and Kramer present concepts, techniques and problems through a variety of forms: informal descriptions, illustrative examples, abstract models and concrete Java examples. These combine to provide problem patterns and associated solution techniques which enable students to recognise problems and arrive at solutions. New features include: *New Chapter and coverage of Verification. *More student exercises. *Totally updated version of the LTSA tool packaged with the book which makes it easier to use and extends its capabilities.
Keywords: Java (programmeertaal).; Object-georiënteerd programmeren; Parallelmethoden; Programmeren